(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This research aimed to assess the economic and social conditions of displaced persons in Hama, comparing their situation before and after displacement. A descriptive-analytical approach was used. To achieve this objective, the researcher designed a questionnaire consisting of 33 statements divided into two sections: (social reality, economic reality). The questionnaire was administered to a sample of 410 displaced persons distributed across Hama. The research findings revealed that displacement had negative impacts on various economic and social aspects of life for displaced residents of Hama Governorate. In terms of human rights, this manifested as a lack of security and stability, and difficulty adapting to the new environment. In education, the results showed a decline in enrollment in public schools, coupled with a decrease in the quality of education due to overcrowded classrooms. In the health sector, the quantity of services provided decreased, along with reduced healthcare support and the destruction of basic infrastructure. The findings also demonstrated significant negative differences in the assessment of the economic situation before displacement compared to the economic situation after displacement, resulting from decreased income levels, fewer job opportunities, and a substantial increase in the cost of living.